Rabbit models for the study of human atherosclerosis: From pathophysiological mechanisms to translational medicine - Fan, Jianglin; Kitajima, Shuji; Watanabe, Teruo; Xu, Jie; Zhang, Jifeng; Liu, Enqi; Chen, Y. Eugene (Pharmacology & therapeutics (Oxford), 2015)
Laboratory animal models play an important role in the study of human diseases. Using appropriate animals is critical not only for basic research but also for the development of therapeutics and diagnostic tools. Rabbits are widely used for the study of human atherosclerosis. Because rabbits have a unique feature of lipoprotein metabolism (like humans but unlike rodents) and are sensitive to a cholesterol diet, rabbit models have not only provided many insights into the pathogenesis and development of human atherosclerosis but also made a great contribution to translational research. In fact, rabbit was the first animal model used for studying human atherosclerosis, more than a century ago. Currently, three types of rabbit model are commonly used for the study of human atherosclerosis and lipid metabolism: (1) cholesterol-fed rabbits, (2) Watanabe heritable hyperlipidemic rabbits, analogous to human familial hypercholesterolemia due to genetic deficiency of LDL receptors, and (3) genetically modified (transgenic and knock-out) rabbits. Despite their importance, compared with the mouse, the most widely used laboratory animal model nowadays, the use of rabbit models is still limited. In this review, we focus on the features of rabbit lipoprotein metabolism and pathology of atherosclerotic lesions that make it the optimal model for human atherosclerotic disease, especially for the translational medicine. For the sake of clarity, the review is not an attempt to be completely inclusive, but instead attempts to summarize substantial information concisely and provide a guideline for experiments using rabbits.